2014
DOI: 10.2190/ec.50.4.c
|View full text |Cite
|
Sign up to set email alerts
|

Exploring E-Learning Acceptance among University Students in Thailand: A National Survey

Abstract: This study surveys the e-learning acceptance of university students in Thailand. One thousand nine hundred and eighty-one (1,981) participants completed the E-Learning Acceptance Measure (Teo, 2010) which measures three constructs that predict e-learning acceptance (tutor quality, perceived usefulness, and facilitating conditions). Data analysis was performed using structural equation modeling (SEM). The results of this study showed that the three constructs were significant predictors of e-learning acceptance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Hence, for the successful use of the LMS, it is important to understand the determinants that impact the real usage of the LMS. Studies have revealed that the real implementation of LMS has not been fully studied in SSA nations [9], and even, the scanty studies on LMS have focused on technical issues ignoring inquiries on the determinants that impact users' real application of LMS [10]. These identified gaps have motivated the researchers to research into the determinants that affect the learners' actual application of LMS.…”
Section: Astesj Issn: 2415-6698mentioning
confidence: 99%
“…Hence, for the successful use of the LMS, it is important to understand the determinants that impact the real usage of the LMS. Studies have revealed that the real implementation of LMS has not been fully studied in SSA nations [9], and even, the scanty studies on LMS have focused on technical issues ignoring inquiries on the determinants that impact users' real application of LMS [10]. These identified gaps have motivated the researchers to research into the determinants that affect the learners' actual application of LMS.…”
Section: Astesj Issn: 2415-6698mentioning
confidence: 99%
“…The students quickly adjusted to the new situation, as previous studies have noted (Teo et al 2014, Bhatiasevi and Naglis 2015, Kew et al 2018. Issues that students faced were mainly due to their unfavourable socio-economic condition.…”
Section: Gaps In Online Accessmentioning
confidence: 83%
“…Students found it difficult to access online resources due to the first two factors i.e., internet availability, and accessibility to own gadgets. The students in Thailand are adaptable to these changes (Teo, 2014), however, the lack of government assistance, the online classroom system was found to be ineffective. Social media is impacting the studies of the student as a resource whereas the hybrid classroom was found to be inadequate as teachers were not able to teach and include all the students at the same time.…”
Section: Resultsmentioning
confidence: 99%